Deprescription in Advanced Cancer Patients - Ferraz Gonçalves (MDPI AG, 2018)
The use of multiple drugs is often referred to as polypharmacy, although this term has not been precisely defined. Frequently, drugs are used unwisely in multiple combinations increasing the risk of adverse reactions, or for the long-term prevention of diseases in patients with a short life expectancy who, therefore, will not benefit from them. The reflection on this has led to the introduction of the concept of deprescription. There are many reasons for the inappropriate drug prescription and barriers to reduce medications. Tools were developed to help prescribers to limit the number of prescribed drugs that patients are taking. Several studies have shown that deprescription of some drugs is possible and safe and can even have a positive influence on wellbeing, cognitive function, falls, and admission to a hospital. Deprescription should be individualized and carried out, as far as possible, in agreement with patients and their families. A six-step method for deprescription is proposed.